Bio-Compatible Sensor for Middle Ear Pressure Monitoring on a Bio-Degradable Substrate - Mosshammer, Klara; Lüdke, Theresa; Spitzner, Sarah; Firzlaff, Daniel; Harre, Kathrin; Kleemann, Hans; Neudert, Marcus; Zahnert, Thomas; Leo, Karl (Frontiers in Electronics, 2021)
Hypotension in the middle ear can cause serious diseases and hearing disorders. Until now, pressure in the middle ear is measured indirectly by using the impedance of the tympanic membrane (tympanometry). Direct methods are just described in scientific studies and would be harmful in clinical routine. Here, we demonstrate a bio-compatible pressure sensor, which can resolve pressure changes in the range of -7.5 kPa up to +7.5 kPa, and due to its compact design (area of 2 x 4 mm²), can be directly implanted in the human middle ear. Furthermore, the read-out of the pressure sensor can be conveniently done using wireless data communication technologies employing a plate capacitor with an elastic dielectric for pressure monitoring and a planar coil. Thus, our sensor allows for direct pressure measurements in the middle ear, avoiding additional surgeries after device implantation.